FRAMING ANALYSIS OF REPORTING ON THE CORRUPTION CASE OF LANGKAT GOVERNOR IN ONLINE MEDIA WASPADA.CO.ID - Maulana Andinata Dalimunthe; Cici Handayani Br Ginting (Universitas Gunadarma, 2023)
This research entitled “Analysis Framing of Corruption Case of Langkat’s Government Terbit Rencana Perangin Angin in Online Media Waspada.co.id”. The research method is qualitative. The study aims to determine how online media waspada.co.id framed the corruption case of Langkat’s Government Terbit Rencana. The subject researched is online media waspada.co.id. The object researched is the news article about the corruption case of Langkat’s Government, Terbit Rencana, released on January 19 and January 20, 2022. The data collection used is a literature study and documentation. The analysis data used is analysis framing Robert N.Entman. The research shows that waspada.co.id framed the